Evaluation of ERG Responsive Proteome in Prostate Cancer - Tan, Shyh-Han (2013)
BACKGROUND: Gene fusion between TMPRSS2 promoter and the ERG proto-oncogene is a major genomic alteration found in over half of prostate cancers (CaP), which leads to aberrant androgen dependent ERG expression. Despite extensive analysis for the biological functions of ERG in CaP, there is no systematic evaluation of the ERG responsive proteome (ERP). ERP has the potential to define new biomarkers and therapeutic targets for prostate tumors stratified by ERG expression. METHODS: Global proteome analysis was performed by using ERG (+) and ERG (−) CaP cells isolated by ERG immunohistochemistry defined laser capture microdissection and by using TMPRSS2-ERG positive VCaP cells treated with ERG and control siRNA. RESULTS: We identified 1196 and 2190 unique proteins stratified by ERG status from prostate tumors and VCaP cells, respectively. Comparative analysis of these two proteomes identified 330 concordantly regulated proteins characterizing enrichment of pathways modulating cytoskeletal and actin reorganization, cell migration, protein biosynthesis, and proteasome and ER-associated protein degradation. ERPs unique for ERG (+) tumors reveal enrichment for cell growth and survival pathways while proteasome and redox function pathways were enriched in ERPs unique for ERG (−) tumors. Meta-analysis of ERPs against CaP gene expression data revealed that Myosin VI and Monoamine oxidase A were positively and negatively correlated to ERG expression, respectively. CONCLUSIONS: This study delineates the global proteome for prostate tumors stratified by ERG expression status. The ERP data confirm the functions of ERG in inhibiting cell differentiation and activating cell growth, and identify potentially novel biomarkers and therapeutic targets.